Holocene Relative Sea-Level Change on the Isle of Skye, Inner Hebrides, Scotland. (2nd January 2016) - Selby, Katherine Anne; Smith, David Edward
ABSTRACT: Holocene relative sea-level (RSL) changes are described for the Isle of Skye, based upon evidence from isolation basins and back barrier environments. RSL rose across low-lying coastal areas in the early Holocene, inundating isolation basins in the Sleat peninsula, and then fell back in the early-middle Holocene before a fluctuating rise occurred later in the middle and late Holocene. A short-lived marine inundation at one site may have been caused by an episode of rapid RSL rise after the discharge of Lakes Agassiz–Ojibway in North America and/or the Holocene Storegga Slide tsunami, generated by submarine landsliding off South-West Norway. The empirical evidence for RSL change on Skye is compared with a recent shoreline-based glacio-isostatic adjustment model, which includes Skye, showing altitudes for the Holocene Storegga Slide tsunami, Main Postglacial, Blairdrummond and Wigtown shorelines in the area. The empirical evidence is shown to be in accord with the altitudes predicted by the model.